PENERAPAN METODE WEIGHTED MOVING AVERAGE UNTUK PERAMALAN PERSEDIAAN PRODUK FARMASI: Array - Silvya, Zihan; Zakir, Ahmad; Irwan, Dedy (JiTEKH, 2020)
Asean Pharmacies often have difficulty in predicting future product inventory based on previously recorded data. Forecasting is very influential on the decision of the pharmacy owner to determine the number of pharmaceutical products that must be provided by the pharmacy. These problems can be solved by the Forecasting technique using the weighted moving average method to predict how many stocks of goods must be purchased for the next period. Calculation of forecasting for future periods is based on previous quarterly data calculations and can also be done based on the selection of desired periods. The purpose of this research is to build a system in predicting future sales value to increase revenue. The system will be built with the Php programming language and use the Unified Modeling Language to design the system workflow